Influence of shock pressure and profile on the microjetting from a grooved Pb surface. (15th December 2016) - Shao, Jian-Li; Wang, Pei; He, An-Min
Abstract: This work investigates the shock-induced microjetting from a grooved surface (10 nm, 120 degree) of low-melting metal Pb with molecular dynamics simulations. The microjetting processes under surface/release melting conditions are presented in detail, and some properties on the microjet mass and velocity are revealed for different shock pressure and profile cases. It is found that the increase of microjet mass with shock pressure experiences three stages: rapid increase (solid phase), slowdown increase (release melting) and almost no increase (shock melting). For all cases, the ratio of the maximal jetting velocity to the surface velocity approximately keeps a constant (1.5–1.55), but this value undergoes a degree of exponential decay with time for the solid release cases. In addition, the temperature of the microjet is found to be always above the melting point (zero pressure) and keep a continuous increase towards the microjet tip. When introducing slow decaying profiles, the microjet mass begins to increase with the decay rate, which is dominated by the deformation of bubble during pull-back. When the decay rate becomes fast enough, the microspall occurs as expected, meanwhile the microjet appears to reduce because of the shock energy reduction. But that cannot cut off the microjet completely. The velocity distribution along the loading direction shows two linear regions corresponding to the microspall and microjet, and the latter seems to have a greater velocity gradient.